What makes the guests choose Airbnb again? The role of guests' experiences in Airbnb home-sharing service quality dimensions toward guests' loyalty in Malaysia - Jefferson Empaling ak Jonathan Jana; Zurinawati Mohi (Bahasa Indonesia, 2026)
With their unique features and characteristics, the rise of home-sharing e-booking applications, such as Airbnb, in Malaysia appears to have a significant impact on the hotel industry. However, several issues relating to security, service delivery, legality, and regulations have appeared. The quality of the service offered remains an essential competitive factor for any type of lodging, including Airbnb home-sharing properties. Thus, this study aims to investigate the influence of Airbnb home-sharing service quality dimensions on guests' experiences and loyalty, and to identify whether these services have the potential to sustain and compete in the hotel industry. With the aid of previous literature, three primary dimensions, i.e., physical environment quality, assurance quality, and interaction quality, along with their sub-dimensions, were identified as key factors for Airbnb home-sharing service quality in Malaysia. A total of 318 complete questionnaires were successfully collected. The sub-dimensions are verified by using exploratory factor analysis (EFA). Regression analysis was conducted following EFA. The results indicate that the Airbnb home-sharing service quality dimension, which includes physical environment quality, assurance quality, and interaction quality, can enhance guests' experience and loyalty. Hence, the findings are expected to enhance service quality and contribute to the body of knowledge that can be replicated in various service industries.